Evaluasi Ketersediaan Infrastruktur Kawasan Agropolitan di Kecamatan Kauditan - Sheren Suenaung; Surijadi Supardjo; Amanda Sembel (Universitas Sam Ratulangi, 2021)
According to RTRW of North Minahasa in 2013-2033, Kauditan subdistrict is designated as one of the subdistricts included in the Klabat Agropolitan Area. Besides having to have superior commodities, Agropolitan Areas must also be supported by adequate agricultural sector infrastructure. Lack of supporting infrastructure has overwhelmed farmers to increase their agricultural production. This study aims to identify the development of the agropolitan areaâ€™s infrastructure, as well as evaluate the availability of infrastructure in the agropolitan area in the Kauditan subdistrict. The analysis method used is Time Series analysis method, and qualitative descriptive analysis that will use a Likert Scale as a rating scale, with indicators such as infrastructure conditions, comparison with standards, and fulfillment of needs. The result of the analysis show that the infrastructure of the agropolitan area that has developed in the Kauditan subdistrict is farm road and irrigation, meanwhile the jetty and collecting sub-terminal are not experiencing any development, and the result of the evaluation of the agropolitan areaâ€™s infrastructure in Kauditan subdistrict show a value of 35,53% or in the â€œbadâ€ category. This value occurs because even though the farm road already â€œvery goodâ€, the evaluation results for irrigation are still â€œbadâ€, the the unavailability of collecting sub-terminals are also affects the overall results. The jetty is not available inKauditan subdistrict, also actually not needed because the Kauditan subdistrict not near the lake or the sea. Keyword: Evaluation; Infrastructure; Agropolitan Areas